Leveraging public health infrastructures to support sexual health for women living in the Southern United States - Pratt, Madeline C.; Thomas, Tammi F.; Merriweather, Anthony; Deaterly, Caroline; Johnson, Bernadette; Hightow-Weidman, Lisa; Hurwitz, Kathleen E.; Bennett, Kara; Rathnayaka, Nuvan; Budhwani, Henna; Rana, Aadia; Nassel, Ariann; et al. (Frontiers in Medicine, 2025)
BackgroundCamellia is a single-arm longitudinal cohort study. We engaged a Community Advisory Board to support refinement of an existing mHealth app platform for use among cis- and transwomen in Alabama, one of seven states prioritized in the federal Ending the HIV Epidemic (EHE) strategy. We partnered with the Alabama Department of Public Health to recruit from a database of women recently diagnosed with gonorrhea or syphilis, aged 18–50, across Alabama. Potential participants are recruited by telephone. A home-based HIV and sexually transmitted infection (STI) testing program allows the study to offer tailored sexual health information, testing, linkage to care and support while assessing STI and HIV incidence and associated predictors.MethodsStudy participants are enrolled into the digital Camellia Cohort in which they complete home-based HIV and STI testing and online surveys every 6 months. Participants are followed for at least 24 months or until study completion (up to 42 months). Primary outcomes include predictors, mediators and moderators for HIV and STI incidence and pre-exposure prophylaxis (PrEP) use via self-report, medical record review, and dried blood spots.ConclusionThe Camellia Cohort integrates epidemiologic methods, mHealth technology, and data science to better characterize HIV transmission dynamics and engagement in the prevention care cascade among women in an EHE focus state. This study will provide critical insights into the feasibility and acceptability of a remote, light-touch cohort design, while also providing data on STI and HIV incidence, PrEP use, and key mediators and moderators influencing prevention behaviors among women with indications for PrEP in this high-priority region.